A case of clinical manifestation of X-linked retinoschisis – in the one eye, and choroidal neovascularisation – in the second eye, in two family members - Siwińska, Magdalena; Michalewski, Janusz; Cisiecki, Sławomir; Nawrocki, Jerzy; Michalewska, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Description of long-time observation of X-linked retinoschisis coexisting with choroidal neovascularization in two brothers. Material and methods: 27-year-old man reported sudden visual impairment in one eye. The same symptoms had patient’s brother. Ophthalmic examination and imaging studies were performed. Results: The diagnosis was made based on clinical features and imaging examinations. Conclusions: This case is unusual. At present there is no effective therapy.